THE DETERMINANTS OF ISLAMIC BANK NET PROFIT MARGIN: EVIDENCE FROM MALAYSIA - MAISYARAH BINTI STAPAH @ SALLEH (Universiti Malaysia Terengganu, 2022)
As a higher net profit margin (NPM) is typically connected to higher financing and lower deposit rates, the NPM level established by Islamic banks [following the maslahah (benefit) element] should protect the benefits of banks, borrowers, and depositors. As such, this research investigated the NPM determinants in Malaysian Islamic banking between 2008 and 2017. Resultantly, the Malaysian Islamic bank NPM was positively associated with bank-specific variables (risk aversion or RA, operating cost or OC, and liquidity or LQ). On another note, saving deposit or SAV, fixed deposit or FD, gross domestic product growth or GDP Growth, and inflation or INF adversely influenced NPM. Additionally, the effect of several financing contracts on NPM revealed that only the bai bithaman ajil (BBA) financing contract was substantially connected to NPM. The second research objective implied that the net interest margin (NIM) of conventional parent banks proved insignificant to the Islamic bank NPM. Objectives 1 and 2 were assessed with static panel data, while the remaining objectives were evaluated using either an independent t-test or the Mann Whitney test. As for objective 3, a difference was identified in the NPM charged by Islamic subsidiary and full-fledged Islamic banks where Islamic subsidiary banks imposed lower NPM (on average) than the full-fledged counterparts. Regarding objective 4, a difference was identified in the NPM charged by foreign Islamic and domestic Islamic banks where foreign Islamic banks imposed a higher (on average) NPM than domestic Islamic counterparts. Summarily, the variables affecting NPM need to be controlled by the Islamic banks in order to attain the maslahah (benefit) of all parties. Bank-specific variables also contributed to the NPM differences offered by the subsidiary, full-fledged, domestic, and foreign Islamic banks. In this vein, Islamic banks needed to develop NPM from an Islamic viewpoint based on the fundamental theory (Contract Theory or CT). This research also outlined how the variables originated from a combination of several theories facilitating the current NPM theory.